2013
DOI: 10.4081/jphr.2013.e2
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls, Glycaemia and Diabetes in a Population Living in a Highly Polychlorinated Biphenyls-Polluted Area in Northern Italy: A Cross-Sectional and Cohort Study

Abstract: Conflicts of interests: the authors declare no potential conflict of interests.BackgroundPolychlorinated biphenyls (PCBs) have been found to be associated with diabetes in some, but not all, studies performed so far. The aim of this study was to assess the association between PCB serum levels and glycaemia and diabetes in people living in Brescia, a highly industrialised PCB-polluted town in Northern Italy.Design and Methods527 subjects were enrolled in a cross-sectional population-based study: they were inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
2
0
0
Order By: Relevance
“…While we did not previously detect an association of PCBs with incident diabetes, the current analysis revealed increased diabetes risk with PCB exposure. The association of PCBs with incident diabetes is consistent with some (Lee et al 2010;Lee et al 2011;Vasiliu et al 2006;Wu et al 2013), but not all prospective investigations on this topic (Rignell-Hydbom et al 2009;Zani et al 2013). …”
Section: Discussionsupporting
confidence: 81%
“…While we did not previously detect an association of PCBs with incident diabetes, the current analysis revealed increased diabetes risk with PCB exposure. The association of PCBs with incident diabetes is consistent with some (Lee et al 2010;Lee et al 2011;Vasiliu et al 2006;Wu et al 2013), but not all prospective investigations on this topic (Rignell-Hydbom et al 2009;Zani et al 2013). …”
Section: Discussionsupporting
confidence: 81%
“…In our study, we found no association between total PCB serum levels, PCB 153 and PCB functional groups and diabetes, hypertension and thyroid diseases when also performing stratified analyses according to gender, age, and BMI. Overall, these findings are in agreement with those from our 2003 cross-sectional survey (Donato et al, 2006, 2008; Zani et al., 2013). In our population, however, medium- and high-chlorinated PCBs contributed most to the total PCBs, whereas dioxin-like PCBs and low chlorinated PCBs, which were the only PCB congeners associated with diabetes and hypertension in some studies, contributed less than 5% to the sum of total PCBs, in agreement with the pattern of PCB congeners assayed in most studies carried out in Western countries.…”
Section: Discussionsupporting
confidence: 91%